Stability of drugs in solid dispersion systems - Chaudhry, Ikram-Ul-Haq; Concha, Jesusa A.; De Castro, Natividad F.
Solid dispersions of aspirin and ascorbic acid in polyethylene glycols 4000 and 6000, at three concentration levels (5, 10 and 15% w/w) were prepared by fusion method. The dispersion systems, at solid state as well as in aqueous medium, were stored under various conditions of temperature to investigate the effects of aging on the chemical stability of aspirin and ascorbic acid. The kinetics of decomposition of aspirin as well as ascorbic acid were also determined. Both the polymers seemed to protect aspirin, but to a very small extent, against hydrolytic degradation. The degradation of aspirin with or without polymers in buffer solution appeared to follow first-order kinetics and the reaction was temperature dependent. The initial concentration of ascorbic acid seemed to influence the decomposition reaction greatly. The decomposition of ascorbic acid showed a decrease with an increase in concentration. Both the polymers appeared to protect ascorbic acid significantly from oxidation degradation in aqueous solution. However, no distinction or rank order of the effect on the degradation of ascorbic acid by the two polyethylene glycols could be found at any of the temperatures studied. Half-life of ascorbic acid in solid dispersions was increased two-fold (approximately) at all the temperatures. Shelf-life of ascorbic acid in aqueous medium has also been predicted at 30, 25 and 20°C by the use of Arrhenius plots. The thermal degradation of ascorbic acid alone or in dispersion systems also followed a first-order reaction and the reaction was temperature dependent.
Keywords: Solid dispersion systems; Drug stability